PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN: (Studi Kasus Kokapura Ahmad Yani Semarang) - Dwi Maharani; Rezty Fauziah Novianti (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
Quality human resources and effective managerial skills are crucial elements in driving employee performance, which ultimately determines the success of a business in achieving its goals. The main problems identified in this study are the presence of unwise leaders, bad habits in the organization, and lack of punctuality at work. Management must recognize and embrace human resources as the most important strategic component. This will ensure that goals are achieved on time and accordingly. The purpose of this study was to determine how the influence of employee performance, organizational culture and work discipline on employee performance. Quantitative method is a research method used to determine the relationship between variables through data collection that can be counted or measured numerically. Quantitative research focuses on measuring and analyzing numerical data, with the aim of describing phenomena, testing hypotheses, and making generalizations or conclusions that apply broadly. This study uses saturated sampling technique with a population of 21 people. The comparison of the significance value with the error rate determined at 0.05 is 0.017 <0.05. Based on this, it can be concluded that the alternative hypothesis (H4) in this study is accepted, while the null hypothesis (Ho4) is rejected.